Research on the operation characteristics of a free-piston linear generator: Numerical model and experimental results. (1st January 2017) - Guo, Chendong; Feng, Huihua; Jia, Boru; Zuo, Zhengxing; Guo, Yuyao; Roskilly, Tony
Highlights: The operation process of free-piston linear generator is investigated. The larger the motor force at the starting process, the fewer circulations of the piston reciprocating to meet ignition condition. The "gradually switching strategy" is the best strategy in the intermediate process. During the generating process, engines indicated power is 2.9 kW with an efficiency of 37.3% under medium load. Abstract: Free piston linear generator (FPLG) shows unique operation characteristics due to the elimination of crankshaft and connecting rod mechanism. This paper investigates its operation characteristics during each operating process based on the simulation and experiment results. During the starting process, the larger motor force during the starting process, the fewer times of reciprocating pistons which meet the condition of ignition. When the motor force reached 300 N, the prototype could adopt one-stroke starting strategy. During the intermediate process, it was found that the "gradually switching strategy" could help to achieve a smoother operation during the intermediate process. And the values of the operation parameters after the intermediate process were lower than those before the intermediate process. During the generating process, cycle-to-cycle variations were observed for piston TDC and in-cylinder gas pressure from the experimental results. According to the experimental results of the FPLG during the generating process, the calculated engine indicated power is 2.9 kW, and the corresponding indicated thermal efficiency is 37.3%. Additionally, based on the comparison of the FPLG performance, it is found that the parameters of the FPLG during the generating process are smaller than those when it was operated during the second stage of the starting process, while much higher than those during the first stage of the starting process.